Hematological Toxicity in Mice after High Activity Injections of 177Lu-PSMA-617 - Amanda Kristiansson; Oskar Vilhelmsson Timmermand; Mohamed Altai; Joanna Strand; Sven-Erik Strand; Bo Åkerström; Anders Örbom (MDPI AG, 2022)
Prostate cancer (PC) is one of the most common malignancies affecting men, with poor prognosis after progression to metastatic castration-resistant prostate cancer (mCRPC). Radioligand therapy (RLT) targeting the overexpressed PSMA on PC cells, with, e.g., 177Lu-PSMA-617, has been effective in reducing tumor burden and prolonging survival in mCRPC. However, it is not a curative method with kidney and bone marrow toxicity limiting the activity given to patients. Previous preclinical models have reported transient hematotoxicity for up to 120 MBq. This activity may still be too low to investigate the effect on renal function since it corresponds to an absorbed dose below 10 Gy, whereas the kidneys in a clinical setting usually receive an absorbed dose more than double. Here we investigated the hematotoxicity and recovery after administered activities of 120, 160, and 200 MBq in a 177Lu-PSMA-617 BALB/cAnNRj mouse model. The animals had an initial drop in white blood cells (WBC) starting 4 days post injection, which recovered after 21 days. The effect on red blood cells (RBC) and platelets was detected later; 17 days post-injection levels decreased compared to the control group. The reduction was restored again 32 days post injection. No correlation between injected activity and hematotoxicity was found. Our results suggest that activities up to 200 MBq of 177Lu-PSMA-617 give transient hematotoxicity from which animals recover within a month and no radiation-related deaths. Injecting these high activities could allow animal studies with increased clinical relevance when studying renal toxicity in animal models.